The Use of Local Anesthesia for Relief of Postoperative Pain After Laparoscopic Cholecystectomy (Iraqi Journal of Medical Sciences, 2022)
Background: The postoperative pain remains the most prevalent complaint after laparoscopic cholecystectomy for cholelithiasis, which may lead to prolong hospital stay.Objective: To evaluate the effect of wound infiltration and intraperitoneal instillation of Bupivacaine for relief the postoperative pain (within first 24 hours) in patient undergoing laparoscopic cholecystectomy.Methods: A randomized study included 60 patients having symptomatic gallstones attending Al-Yarmouk Teaching Hospital, Department of Surgery, Baghdad, Iraq, during the period from December 2018 to December 2019; for elective laparoscopic cholecystectomy. Patients were divided into two equal groups; in group (A), intraperitoneal 10 ml bupivacaine (0.5%) was given for postoperative pain relief, while group (B) was not given this local anesthesia. The postoperative pain was assessed by Visual Analogue Scale score at fixed time intervals starting 1, 2, 4, 6 hrs then 12, 18 and 24 hrs postoperatively.Results: In group A, 33.3% (n=10) of patients had abdominal pain that needed additional analgesia, while 66.6% (n= 20) of patients, they didn’t need additional analgesia. In group B, 93.3% (n=28) of patients had pain and needed additional analgesia, whereas 6.6% (n=2) of patients, they didn’t need additional analgesia. The incidence of shoulder pain was 10% (n=3) in group A and 20% (n=6) in group B.Conclusion: The wound infiltration and intraperitoneal instillation of local anesthesia significantly reduces abdominal pain (first 12 hrs), also reduces the need for post-operative additional analgesia, while local anesthesia had no significant effect on shoulder tip pain, post operatively.Keywords: Laparoscopic cholecystectomy, local anesthesia, post operative painCitation: Malallah ZZ, Al-Mafrachi KKR. The use of local anesthesia for relief of postoperative pain after laparoscopic cholecystectomy. Iraqi JMS. 2022; 20(1): 98-105. doi: 10.22578/IJMS.20.1.13
Keywords: Laparoscopic cholecystectomy; local anesthesia; post operative pain